A Review: Preparation, Performance, and Applications of Silicon Oxynitride Film - Yue Shi; Liang He; Fangcao Guang; Luhai Li; Zhiqing Xin; Ruping Liu (Micromachines, 2019)
Silicon oxynitride (SiNxOy) is a highly promising functional material for its luminescence performance and tunable refractive index, which has wide applications in optical devices, non-volatile memory, barrier layer, and scratch-resistant coatings. This review presents recent developments, and discusses the preparation methods, performance, and applications of SiNxOy film. In particular, the preparation of SiNxOy film by chemical vapor deposition, physical vapor deposition, and oxynitridation is elaborated in details.